Should We Consider Patients with Coexistent Hepatitis B or C Infection for Orthotopic Heart Transplantation?. (7th November 2013) - Sekar, Baskar; Newton, Pippa J.; Williams, Simon G.; Shaw, Steven M.
Abstract : Heart transplantation (HTX) is the gold standard surgical treatment for patients with advanced heart failure. The prevalence of hepatitis B and hepatitis C infection in HTX recipients is over 10%. Despite its increased prevalence, the long-term outcome in this cohort is still not clear. There is a reluctance to place these patients on transplant waiting list given the increased incidence of viral reactivation and chronic liver disease after transplant. The emergence of new antiviral therapies to treat this cohort seems promising but their long-term outcome is yet to be established. The aim of this paper is to review the literature and explore whether it is justifiable to list advanced heart failure patients with coexistent hepatitis B/C infection for HTX.